2006
DOI: 10.1021/ie060348o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Divalent Cations and Surfactants on Silica−Bitumen Interactions

Abstract: In oil sands processing, the separation of bitumen from sand grains is controlled by interfacial interactions between the bitumen and the sand. In this study, the effects of calcium and magnesium cations, surfactants, and their combination on the sand−bitumen interactions and consequently on bitumen liberation were investigated. Surface forces between silica and bitumen in industrial-plant process water and in water containing calcium and magnesium in amounts equivalent to those found in the plant process wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…12,[18][19][20][21][22][23] The technique has identified specific conditions which promote slime coating of montmorillonite on bitumen and coal in the presence of divalent cations. 18,46 Therefore, the interaction between montmorillonite, with bitumen in the absence and presence of calcium was Optical microscope and SEM images of the sensor surface were analyzed after completion of the QCM-D experiments to confirm slime coating of montmorillonite clay particles on bitumen immobilized on silica sensor.…”
Section: Qcm-d Methods Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[18][19][20][21][22][23] The technique has identified specific conditions which promote slime coating of montmorillonite on bitumen and coal in the presence of divalent cations. 18,46 Therefore, the interaction between montmorillonite, with bitumen in the absence and presence of calcium was Optical microscope and SEM images of the sensor surface were analyzed after completion of the QCM-D experiments to confirm slime coating of montmorillonite clay particles on bitumen immobilized on silica sensor.…”
Section: Qcm-d Methods Evaluationmentioning
confidence: 99%
“…[14][15][16] The mechanism for bitumen slime coating has recently been studied in detail by Masliyah et al using atomic force microscopy (AFM) and zeta potential distribution measurement. 12,[17][18][19][20][21][22][23] While oil sands ores are a complex mixture of clays including kaolinite, illite, chlorite, montmorillonite, not all the clays cause slime coating. By systematically studying model clays, researchers have shown the detrimental impact of montmorillonite and illite, although to a less extent, on bitumen recovery by slime coating.…”
Section: Introductionmentioning
confidence: 99%
“…[30] A brief summary of the systems considered and the main findings are provided in Table 1. Zhao et al [33] Bitumen -silica (Oil sands processing) 1] Strong attraction leading to heterocoagulation of bitumen and silica measured in 1 mM KCl at pH 10.5 with 1 mM calcium addition. The strong adhesion and long range attraction as verified by AFM contribute to poor bitumen liberation from sand grains.…”
Section: Measuring Interaction Potential By Electrophoretic Mobility mentioning
confidence: 99%
“…However, previous research has shown excellent agreement between zeta potential distributions of binary mixtures and interaction forces as measured by AFM. [33] Due to its versatility to determine particle interactions of complex multicomponent systems where highly sophisticated surface forces apparatus and atomic force microscope cannot be used, the zeta potential distribution measurement was used in the current study to determine attachment characteristics between sub-micron size gas bubbles and solid (silica and alumina) particles. The degree of attachment was controlled by varying the electrostatic and hydrophobic forces.…”
Section: Measuring Interaction Potential By Electrophoretic Mobility mentioning
confidence: 99%
“…Effect of temperature on the interfacial tension for the bitumen/aqueous phase measured at various pH values (Drelich, 1993) bitumen, sand (silica), fines and various clays by zeta potential measurement have been carried out at ambient temperature (Liu et al, 2002(Liu et al, , 2003(Liu et al, , 2004a(Liu et al, , b, 2005aMasliyah, 1994;Chow, 1983, 1985;Takamura and Isaacs, 1989;Zhao et al, 2006). However, little attention has been paid to the effect of temperature on the zeta potentials of these oil sand constituents.…”
Section: Electric Surface Potentials Of Oil Sand Componentsmentioning
confidence: 99%